Determination of pyrethroids and organochlorine pesticides in oolong tea by gas chromatography-negative chemical ionization-mass spectrometry - ZHU Pan; WAN Huan; LV Fen; YAO Jing; LONG Chaoyang; HUANG Weixiong; WU Yongning (Zhongguo shipin weisheng zazhi, 2021)
ObjectiveTo establish a method for the determination of several kinds of pyrethroids and organochlorine pesticides in Chinese oolong tea samples based on liquid-liquid extraction-solid phase extraction-gas chromatography-negative chemical ionization-mass spectrometry (GC-NCI-MS).MethodsOolong tea samples were crushed and screened, soaked in boiling water, extracted with acetone-n-hexane, purified by Carb-NH2 column, and then identified and quantified by GC-NCI-MS.ResultsAll the 18 kinds of pyrethroids and 9 kinds of organochlorine pesticides showed good linear relationships in range of 0.006-1.00 μg/mL and 0.006-0.50 μg/mL respectively, and the correlation coefficients were above 0.996. The recoveries at different spiked levels for all target compounds in blank matrices were 60.1%-119.8%, and the relative standard deviation (RSD) were 1.5%-10.4% (n=6). The limits of detection and quantification of the method were 0.5-4.8 μg/kg and 1.7-16.0 μg/kg, respectively.ConclusionThe method was suitable for rapid screening and analysis of 18 pyrethroids and 9 organochlorine pesticides in Chinese oolong tea with the advantage of accuracy, rapidity and high sensitivity.